Marcas da enunciação em textos publicitários : o sentido argumentativo de até - Fornari, Tânia Aider Scarton (2007)
Both in mother language teaching and grammar books, greater importance has been given to lexical words also flexional and derivative grammar, relegating to a secondary level, words such as until , mostly because classification difficulties are found by grammar scientists and language teaching aiming linguistic elements classification, and not its observation and function. So they are not noted by students that just memorize and then forget it. But, is known that great text argumentative strength, provides the meaning established by particles used like this. Using until , central issue of this study, grammar tradition concepts are presented, verified in descriptions dictionary and grammar books analyzed, are extremely reducers in relation of its applicability. They are closed descriptions that try to describe all the contexts until may occur. An exhausting and impossible job in which a new title could be created with little detail. This project makes a description of until based on the theory, defended by Ducrot and Anscombre, responsible for the Theory of Argumentation within Language enlarged and modified by Marion Carel with the Theory of the Semantic Blocks saying that argumentation does not constitute something added to linguistic usage, but otherwise, is entered in the own language. Ducrot proposes an instructional conception, more open to signification, when he realized the traditional one, based on information, cannot handle all wording. To study the word until on this project, ten advertising samples were analyzed willing to identify, on verbal texts, semantic blocks formed and selected argumentative aspect, to explicitly instruct the reader to construct the meaning with until . Through this analysis of this adds, on the Theory of the Semantic Blocks perspective is enhanced by the idea that semantic description is instructional, open, showing greater linguistic facts explaining power, if compared to traditional semantic description. It is only on the title that meaning can be established, once linguistic instructions are followed about how it must be read, about argumentative segment value, and the words it contains. So, X to Y structure description, by argumentative semantic, is valorous because allow the understanding of various titles using until